Ethonomedicinal, Antibacterial and Antifungal Potentiality of Centella asiatica, Nerium indicum and Cuscuta reflexa - Widely Used In Tiwa Tribe of Morigaon district of Assam, India. - Debajit Kalita; Jagat Saikia (International Journal of Phytomedicine, 2012)
In Assam, Approximately 17 different types of Tribes are residing from immemorial times. They have lots of knowledge to remedy disease by using various medicinal plants. The aim of our study is to extract out the knowledge of those plants having the medicinal values and examine the laboratory based antibacterial and antifungal property. The selection of these three plants was based on highly uses by the Tiwa Tribes in gastrointestinal troubles and skin diseases. Aquous and 50% ethanolic extract was prepared from the plants and screened against enteropathogenic bacteria E.coli (MTCC723), Bacillus subtilis (MTCC10619) and Staphyllococcus aureus (MTCC96). Antifungal activity were tested against Aspergillus niger and Candida albicans. Centella asiatica and Nerium indicum showed good results against E.coli and Bacillus subtilis and Cuscuta reflexa showed higher activity against S. aureus. In case of antifungal activity, Centella asiatica results were found fruitful in comparison to the others.